Platform Liability for Defective Products under Indonesia's Consumer Protection Law in E-Commerce - Ardiyanti Aris; Lia Trizza F.A; Hamida Hasan; Riza Amalia Rifani (JURNAL SULTAN: Riset Hukum Tata Negara, 2026)
Legal protection for consumers in the e-commerce context has become an increasingly important issue alongside the rapid growth of the online trading industry in Indonesia. This issue encompasses the responsibility of business actors for defective products and the losses experienced by consumers, particularly through platforms such as Shopee, Tokopedia, and Lazada. In practice, platforms tend to define themselves as intermediaries, thereby avoiding direct liability to consumers, even though they control payment systems, logistics, and communication. This article analyzes platform liability under Law No. 8 of 1999 on Consumer Protection (UUPK), examines the effectiveness of dispute resolution by the Consumer Dispute Settlement Agency (Badan Penyelesaian Sengketa Konsumen/BPSK), compares Indonesian regulation with the European Union's General Product Safety Regulation (GPSR) and Australia's Australian Consumer Law (ACL), and recommends revisions to the UUPK to include e-commerce platforms as co-responsible parties. The analysis finds that while the UUPK provides a strong normative foundation, significant enforcement gaps persist. BPSK faces limitations in capacity and authority in handling digitally-based disputes. Effective protection, transparency in return policies, and oversight of third-party sellers are key to creating a safer and more trustworthy online commerce ecosystem.